2013
DOI: 10.1111/jocd.12048
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium‐yttrium aluminum garnet laser versus pulsed dye laser in erythemato‐telangiectatic rosacea: comparison of clinical efficacy and effect on cutaneous substance (P) expression

Abstract: The use of Nd-YAG laser and PDL appears to be safe and effective measures in treatment of erythemato-telangiectatic rosacea. Both types of laser decrease the concentration of substance (P) in the skin. This effect is more pronounced with Nd-YAG laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…Based on the finding that laser treatment in rosacea patients decreases the concentration of substance P in the skin, the authors concluded that substance P may play a central role in the pathophysiology of vascular changes. So far, this phenomenon has been demonstrated for both the PDL and the Nd:YAG laser .…”
Section: Light and Laser Devices For Vascular Changesmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on the finding that laser treatment in rosacea patients decreases the concentration of substance P in the skin, the authors concluded that substance P may play a central role in the pathophysiology of vascular changes. So far, this phenomenon has been demonstrated for both the PDL and the Nd:YAG laser .…”
Section: Light and Laser Devices For Vascular Changesmentioning
confidence: 85%
“…Interessante pathophysiologische Ansätze konnten in letzter Zeit von Lasertherapien abgeleitet und publiziert werden: Aufgrund der Beobachtung, dass nach Lasertherapie eine Reduktion der Substanz P in der papillären Dermis festzustellen ist, kann gefolgert werden, dass Substanz P eine zentrale Rolle in der Pathophysiologie der vaskulären Veränderungen spielen kann. Dieses Phänomen wurde bislang sowohl für den PDL als auch für den Nd:YAG-Laser nachgewiesen [ 14,15 ] . "Flushing"-Ereignisse beschrieben, hierzu gibt es einzelne Beobachtungen, jedoch keine standardisierten Studiendaten [ 11 ] .…”
Section: Farbstofflaser (Pdl)unclassified
“…Recommendation Diffuse erythema and telangiectasia of rosacea can be effectively and safely reduced by the use of LPDL (595 nm) and KTP (532 nm) lasers, and IPLS (GRADE 1A) . Less evidence is available for millisecond and microsecond Nd:YAG (1064 nm) lasers (GRADE 1C) …”
Section: Treatment Of Different Vascular Lesionsmentioning
confidence: 99%
“…Interessante pathophysiologische Ansätze konnten in letzter Zeit von Lasertherapien abgeleitet und publiziert werden: Aufgrund der Beobachtung, dass nach Lasertherapie eine Reduktion der Substanz P in der papillären Dermis festzustellen ist, kann gefolgert werden, dass Substanz P eine zentrale Rolle in der Pathophysiologie der vaskulären Veränderungen spielen kann. Dieses Phänomen wurde bislang sowohl für den PDL als auch für den Nd:YAG‐Laser nachgewiesen .…”
Section: Licht‐ Und Lasertherapien Vaskulärer Veränderungenunclassified